Influence of the alloy composition on determining the millesimal fineness of gold by X-ray fluorescent and assay analysis - Artyukh, Tatyana; Hryhorenko, Inna; Ternova, Alla; Yaheliuk, Svitlana; Cernavca, Mihai (Eastern-European Journal of Enterprise Technologies, 2018)
The conducted studies revealed the influence of the methods of cupellation and the XFA on the accuracy of determining the millesimal fineness in the system of the assay control. The effect of the alloy composition of jewelry alloys on determining millesimal fineness was established. In particular, it was experimentally proved that nickel in combination with zinc as an integrated alloying component substantially changes the cupellation process of gold alloys. This leads to deviation of the millesimal fineness of a gold alloy, determined by cupellation compared with the X-ray fluorescent analysis (XFA) towards a decrease ranging from 0.10 to 0.15 %. The research of gold alloys with the content of nickel with the help of the XFA revealed microalloying by modifiers and actively acting deoxidizing agents (indium, palladium, platinum, etc.). It was established that modifiers are used both separately and in complex, but they do not make a significant impact on determining the millesimal fineness. A number of systemic and random errors in techniques, which affect the results of determining and are related to the technique of performing preparatory operations, as well as analyses operation, were detected. Based on the obtained results, the permanent temperature mode was developed and the procedure of the process of cupellation of gold alloys with the content of nickel was improved with a view to further improvement and metrological certification of the procedure. It was proved that the use of the XFA method for control of millesimal fineness and the content of the component composition of modern gold-based pieces of jewelry and museum values (antiques) is possible not only as the method of screening. The method can replace the touchstone (with obvious advantages), and be an alternative to cupellation. Application of the XFA for current control of millesimal fineness and the content of an alloy of jewelry pieces is advisable to increase up to 30 % (against 2 % in accordance with the current legislation). Its use will make it possible to increase the number of analyzed samples without worsening the trading presentation of the jewelry pieces of a customer